Reliability-based design optimization of a spar-type floating offshore wind turbine support structure. (September 2021) - Leimeister, Mareike; Kolios, Athanasios
Abstract: The application of reliability-based design optimization (RBDO) methods to offshore wind turbine systems is highly relevant regarding economic efficiency and for considering prevailing uncertainties within the design process. Furthermore, RBDO is a very promising approach in optimizing systems when classification and standardization are not fully available. The level of difficulty of design optimization already increases when including the reliability aspect, but becomes even more challenging when dealing with the highly complex system of floating wind turbines (FWTs), which has not yet been applied. Thus, this paper presents for the first time an integrated framework for RBDO of FWTs, combining concepts of optimization with reliability-based design and advanced modeling, requiring reasonable computational effort and time expenditure. In preprocessing, environmental conditions, limit states, and uncertainties are specified, an appropriate reliability assessment approach is elaborated, and response surfaces for various system geometries in the optimization design space are generated ahead of the RBDO execution. These are finally used by means of an interpolation approach for the reliability calculation integrated in the iterative design optimization. On the example of a spar-buoy FWT system, the application of the presented methodology and the feasibility of coupling FWT design optimization with reliability assessment are shown. Highlights: Combining floating wind turbine design optimization and reliability assessment. The developed and presented methodology is the first of its kind. Time efficient realization through a response surface-based interpolation approach. Optimization with integrated limit states, uncertainties, and reliability criteria. Consideration of fully-coupled floating offshore wind turbine system dynamics.